Teaching Reading with KWL Strategy during Online Learning - Widyari, Ni Kadek Riska; Ratminingsih, Ni Made; Saputra, I Nyoman Pasek Hadi (English Education Department STKIP Agama Hindu Singaraja, 2022)
This current study aimed at investigating the effect of KWL strategy towards the reading comprehension of second grade students at SMA N 1 Kintamani in online learning. This research was an experimental research with pre-test and post-test control group design. By involving XI IPS 1 as the control group which taught by using conventional method and XI IPS 2 as the experimental group which taught by using KWL strategy in teaching reading. The obtained data were descriptively and inferentially analyzed by using SPSS 23.0. In pre-test, the study found the experimental group (M= 56.28) showed higher mean score of reading comprehension rather than the control group (55.87). The result of t-test also revealed that the mean difference between experimental and control group in pre-test was not significant (α=>0.05). Furthermore, in post-test the experimental group got better reading comprehension achievement than the control group. The result of the study found that the experimental group (M=74.32) got higher mean score of reading comprehension compared to control group (M= 61.16). The result of t-test also confirmed that the mean difference between experimental and control group in post-test was significant (α=<0.05. In conclusion, KWL strategy gave a significant effect on the reading comprehension of second grade students at SMAN 1 Kintamani.